Heat Pump as an Emission Reduction Measure for Ships: Environmental and Economic Assessment - Malik Kanchiralla, Fayas; Brynolf, Selma; Reis de Oliveira, Dinis Soares (Modelling and Optimisation of Ship Energy Systems 2023, 2024)
Greenhouse gas regulations from the International Maritime Organization, such as the Carbon Intensity Indicator and the Energy Efficiency Existing Ship Index are drawing attention to the implementation of energy efficiency technologies in ships to lower emissions. Presently, more attention is paid to energy efficiency measures related to propulsion (e.g. speed management) and auxiliary energy use (e.g. onshore power). This study compares the environmental impact and cost of replacing heat pumps as an energy efficiency measure instead of oil-fired boilers for two case study vessels by comparing the life cycle impact of different strategies to fulfill the thermal load of vessels while at the port. In terms of life cycle emissions, the heat pump operated using onshore power has the potential to reduce global warming potential by 88% compared to an oil-fired boiler. This accounts for saving 3% and 8% of annual greenhouse gas emissions from entire ship operations, including emissions from engines for the respective case study ships. In addition, shifting to a heat pump avoids NOx and SOx emissions, which adversely affect air quality in the populated areas near the port. Cost results show that the heat pump has an overall higher cost of ownership for case study vessel 1 and a lower cost of ownership for case study vessel 2 compared to oil-fired boiler. Depending on the energy use of specific ships, heat pumps can be cost-competitive at existing carbon emission allowance prices (approximately 90€/tCO2) in the European emission trading system. For the assessed cases, with the emission trading scheme, the return on investment is less than six years and three years for case study vessels 1 and 2 respectively. The study also shows that operating a heat pump is more cost-effective than directly using electro-fuel in a boiler for thermal loads.